A novel in vivo model of puncture-induced iris neovascularization. - Ophélie Beaujean; Filippo Locri; Monica Aronsson; Anders Kvanta; Helder André (PLoS ONE, 2017)
To assess iris neovascularization by uveal puncture of the mouse eye and determine the role of angiogenic factors during iris neovascularization.Uveal punctures were performed on BalbC mouse eyes to induce iris angiogenesis. VEGF-blockage was used as an anti-angiogenic treatment, while normoxia- and hypoxia-conditioned media from retinal pigment epithelium (RPE) cells was used as an angiogenic-inducer in this model. Iris vasculature was determined in vivo by noninvasive methods. Iris blood vessels were stained for platelet endothelial cell adhesion molecule-1 and vascular sprouts were counted as markers of angiogenesis. Expression of angiogenic and inflammatory factors in the puncture-induced model were determined by qPCR and western blot.Punctures led to increased neovascularization and sprouting of the iris. qPCR and protein analysis showed an increase of angiogenic factors, particularly in the plasminogen-activating receptor and inflammatory systems. VEGF-blockage partly reduced iris neovascularization, and treatment with hypoxia-conditioned RPE medium led to a statistically significant increase in iris neovascularization.This study presents the first evidence of a puncture-induced iris angiogenesis model in the mouse. In a broader context, this novel in vivo model of neovascularization has the potential for noninvasive evaluation of angiogenesis modulating substances.